2014
DOI: 10.1021/jf503521m
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metabolite Profiles of Leaves of Bilberry (Vaccinium myrtillus L.) and Lingonberry (Vaccinium vitis-idaea L.)

Abstract: Leaves of bilberry (Vaccinium myrtillus L.) and lingonberry (Vaccinium vitis-idaea L.) are potential raw materials for food and health care products. Targeted (HPLC-DAD, HPLC-MS, and GC-FID) and nontargeted ((1)H NMR) approaches were applied to study the metabolomic profiles of these leaves. Chlorogenic acid was the major phenolic compound in bilberry leaves and arbutin in lingonberry leaves. Flavonol glycosides were another major group of phenolics in bilberry [5-28 mg/g DM (dry mass)] and lingonberry (15-20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 33 publications
5
50
0
5
Order By: Relevance
“…The main classes of phenolic compounds present in the leaves and stems of Vaccinium myrtillus L. and Vaccinium vitis-idaea L. are phenolic acids (mainly chlorogenic acid), flavonoids, flavonol glycosides, and (epi)catechin monomers and oligomers [6,10,12,14,15,17,18], all known to be powerful antioxidants that act by directly trapping ROS, chelating transition metal ions, and inhibiting enzymes involved in the oxidative stress [19,20]. The recent studies conducted by Bujor et al [10,15] showed that phenolic compounds were found in significantly higher contents in the leaves and stems than in the fruits.…”
Section: Phenolic Composition Of Aerial Parts Of Vaccinium Myrtillus mentioning
confidence: 99%
“…The main classes of phenolic compounds present in the leaves and stems of Vaccinium myrtillus L. and Vaccinium vitis-idaea L. are phenolic acids (mainly chlorogenic acid), flavonoids, flavonol glycosides, and (epi)catechin monomers and oligomers [6,10,12,14,15,17,18], all known to be powerful antioxidants that act by directly trapping ROS, chelating transition metal ions, and inhibiting enzymes involved in the oxidative stress [19,20]. The recent studies conducted by Bujor et al [10,15] showed that phenolic compounds were found in significantly higher contents in the leaves and stems than in the fruits.…”
Section: Phenolic Composition Of Aerial Parts Of Vaccinium Myrtillus mentioning
confidence: 99%
“…In bilberry fruits, high amounts of anthocyanins and hydroxycinnamic acid derivatives as well as low amounts of flavonols, proanthocyanidins and coumaroyl iridoids were identified (Mikulic-Petkovsek et al, 2015). In contrast, leaves are known to contain, in decreasing levels, hydroxycinnamic acids, flavonol glycosides and proanthocyanidins but also cinchonains and iridoids in unknown amounts (Liu et al, 2014;Martz et al, 2010). A comparative study conducted by Teleszko and Wojdyło (2015) showed that phenolic compounds were found in a markedly higher content in leaves than in fruits, in agreement with the strongest antioxidant capacity displayed by leaves compared to fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Malonic acid could be grafted on the 4-OH group of pcoumaric acid or on the hexose unit when p-coumaric acid can be either etherified or esterified by the hexose unit, in agreement with the earlier identification of p-coumaric acid-4-O-hexosides and p-coumaroylhexosides, respectively. Compounds with parent ions at m/z 409, 411 and 451 were already found in bud and leaf extracts of bilberry byIeri et al (2013),Liu et al (2014), andMikulic-Petkovsek et al (2015)…”
mentioning
confidence: 96%
“…Metabolomic profiling is powerful in describing the similarities and differences of biological system by exhaustive profiling of metabolites in an organism, which has been used for investigating metabolic differences between plant tissue specific , food safety (Chen et al, 2012;Liu et al, 2014) and disease diagnostics (Wagner, Scholz, Sieber, Kellert, & Voelkel, 2007) recently. This strategy adopts an automated compound extraction algorithm to profile samples at the level of individual molecular fragments without sophisticated peak assignment.…”
Section: Introductionmentioning
confidence: 99%